2017
DOI: 10.1038/eye.2017.33
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the risk of parafoveal scotoma in myopic normal tension glaucoma: role of optic disc tilt and rotation

Abstract: PurposeThe purpose of the study was to evaluate the factors associated with development of parafoveal scotoma in early myopic normal tension glaucoma (NTG).Patients and methodsNinety-nine myopic NTG patients with mean deviation (MD) >-6.0 decibels (dB) were enrolled. Parafoveal scotoma was defined as a visual field (VF) defect within 10° of fixation with at least one point at P<1% lying at the four innermost central points. Systemic factors, optic disc characteristics including tilt ratio, rotation degree, β-z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…The results of the current study agree with these previous reports. [20][21][22] In the current study, both the Drasdo and the Sjöstrand models resulted in better structure-function relationships than those achieved by the no-displacement model, particularly around the fovea. Ohkubo et al 5 compared the pointwise structure-function relationships of patients with glaucoma (average MD value of HFA 10-2 test: -5.49 ± 5.74 dB; range, -20.25 to +2.94 dB) in nonlong AL eyes (more than -6 diopters of myopia) using the Sjöstrand model.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The results of the current study agree with these previous reports. [20][21][22] In the current study, both the Drasdo and the Sjöstrand models resulted in better structure-function relationships than those achieved by the no-displacement model, particularly around the fovea. Ohkubo et al 5 compared the pointwise structure-function relationships of patients with glaucoma (average MD value of HFA 10-2 test: -5.49 ± 5.74 dB; range, -20.25 to +2.94 dB) in nonlong AL eyes (more than -6 diopters of myopia) using the Sjöstrand model.…”
Section: Discussionmentioning
confidence: 91%
“…Araie et al 21 reported that the power of myopia was significantly correlated with depression in the inferior VF of 10-2 test locations in glaucoma eyes. Sung et al 22 reported that among 99 eyes with early myopic normal tension glaucoma, 42 (42.42%) showed scotoma within 10 degrees. As implied by these studies, VF sensitivity tends to decrease as myopia increases, and myopic glaucoma eyes tend to show inferior and parafoveal VF defects.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of myopia has markedly increased over the past three decades, especially in China [ 1 ]. In myopic eyes, there are morphological changes in the optic disc, such as β -peripapillary atrophy ( β -PPA), tilt, and rotation [ 2 ]. The myopic β -PPA, also known as the optic disc crescent, is a white area with a well-defined boundary and visible sclera due to uncovering of the retinal pigment epithelium (RPE), a common structure in myopic eyes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…[16] Sung et al also reported that the greater disc tilt was associated with development of parafoveal scotoma in myopic eyes with early NTG. [17] During myopia progression, eyeball elongation resulted in scleral stretching and tilting of the optic disc. Myopic tilting of the optic disc might strain the temporal side of lamina cribrosa and axons of papillomacular bundle which make papillomacular bundle more vulnerable to glaucomatous damage.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Sung et al also reported that greater disc tilt and lesser disc rotation were associated with the worse parafoveal VF defect in myopic patients with early normal tension glaucoma. [17]…”
Section: Introductionmentioning
confidence: 99%